The Role of the Merdeka Curriculum in Strengthening the Pancasila Student Profile through Islamic Religious Education: A Qualitative Literature Review - Falahain, Muchtar; Santosa, Sedya (Universitas Muhammadiyah Yogyakarta, 2026)
This article explores the role of the Merdeka Curriculum in strengthening the Pancasila Student Profile through Islamic Religious Education in Indonesian schools. Using a qualitative literature review approach, this study synthesizes findings from a wide range of Indonesian academic sources, including journal articles, theses, and national education reports, to analyze how PAI contributes to the internalization of Pancasila values in the context of Merdeka-based learning. The six dimensions of the Pancasila Student Profile, faith and piety, moral integrity, global diversity, cooperation, independence, and critical-creative thinking, are used as an analytical framework. The review revealed that PAI has the potential to serve as a strategic medium for integrating these values through contextualized teaching strategies, such as project-based learning (PBL), reflective discussions, and community-based religious practices. Innovative pedagogies, particularly those that involve digital tools and student-centered projects, play a central role in fostering critical thinking, creativity, and spiritual awareness among students. However, the literature also highlights significant barriers to implementation, including insufficient teacher training, inconsistent policy application, infrastructure limitations, and weak stakeholder coordination. Best practices from successful case studies suggest that strong school leadership, contextualized lesson planning, sustained professional development, and community involvement are essential for optimizing the integration of Pancasila values through PAI. This study concludes that while the Merdeka Curriculum offers transformative potential for character education, its success hinges on collaborative, well-supported, and context-sensitive implementation efforts, particularly in religious education settings.